Neural respiratory drive and symptoms that limit exercise in chronic obstructive pulmonary disease. (26th February 2015) - Jolley, Caroline; Luo, Yuanming; Steier, Joerg; Sylvester, Karl; Man, William; Rafferty, Gerrard; Polkey, Michael; Moxham, John
Abstract: Background: Exercise capacity in chronic obstructive pulmonary disease (COPD) is limited by both breathlessness and leg muscle fatigue. Neural respiratory drive, measured as diaphragm electromyogram (EMGdi) activity expressed as a proportion of maximum (EMGdi%max), quantifies the mechanical load on the respiratory muscles and relates closely to breathlessness. We tested the hypothesis that end-exercise EMGdi%max would be higher in patients stopping because of breathlessness than in those limited by leg fatigue. Methods: EMGdi, ventilation, rate of oxygen consumption (VO2 ), and ventilatory reserve (ventilation/maximum ventilatory volume ratio [VE/MVV]) were measured continuously in patients with COPD during exhaustive cycle ergometry. EMGdi was measured with a multipair oesophageal catheter passed per-nasally. Differences in physiological variables between groups of patients stopping because of breathlessness, leg fatigue, or both were assessed with one-way ANOVA. Findings: 23 patients were included (median FEV1, 39% of predicted, IQR 30·0–56·8). End-exercise EMGdi%max was significantly higher in patients stopping exercise because of breathlessness (n=12, median EMGdi%max 75·7% [IQR 69·5–77·1]) than in those stopping because of leg fatigue (n=8, 44·1 [39·4–63·3]) or both (n=3, 74·1 [63·6–81·2]) (p=0·02). There were no significant differences between the groups in end-exercise ventilation (breathlessness 25·7 L/min [16·3–32·0] vs leg fatigue 31·5 [20·9–39·6] vs both 22·0 [17·7–35·7]), VO2, (13·4 mL/min per kg [11·6–14·2] vs 12·1 [10·4–14·8] vs 9·4 [9·1–12·4]), or VE/MVV (80·4% [72·6–88·3] vs 57·8 [52·1–92·6] vs 63·9 [34·5–88·9]). Interpretation: These results suggest that patients limited by breathlessness due to ventilatory constraints can be identified as those reaching near-maximum levels of neural respiratory drive during exercise. Measurement of EMGdi%max during exercise could prove useful in identifying patients whose functional performance would be best optimised by improvment in pulmonary mechanics rather than interventions to train peripheral muscle groups. Funding: None.